Occurrence and spread of Ceroplastes cirripediformis Comstock (Hemiptera: Coccomorpha: Coccidae) in India - Joshi, Sunil; Bhaskar, Haseena; Poon, V.s. Aashiq; Mala, B.r. Jayanthi; Jayanthi, P.d. Kamala; Pai, Sachin G.; Thite, Sachin V.; Sood, Ajay K.; Kedar, Santosh C.; Sridhar, V.; Deepthy, K.b.; Navik, Omprakash; et al. (Zootaxa, 2021)
The notoriously destructive and invasive soft scale, Ceroplastes cirripediformis Comstock (Hemiptera: Coccomorpha: Coccidae), is recorded for the first time from India. The scale is redescribed to facilitate its identification and information on its host range, natural enemies and distribution is provided. An identification key to the Indian species in this genus is given. Management options in the event of an outbreak are discussed briefly. The establishment of this scale insect warrants special attention in India as it is a potentially damaging plant pest and has a broad host range across many plant families.